FEATURES OF MODERN ENTREPRENEURSHIP IN THE TOURISM AND HOSPITALITY INDUSTRY (Development Service Industry Management, 2023)
Modern challenges and threats to the national security of Ukraine necessitate a radical transformation of approaches to the formation of vectors for the economic development of the state in the conditions of Russian aggression. These approaches should take into account both the rethinking of the existing instruments of state regulation of the economic sector, and the corresponding change in approaches to the management of economic systems at the micro level, namely, business in modern conditions should take into account existing threats and challenges, in order to preserve the possibility of further functioning and development.In the pre-war and pre-war period, enterprises of the tourism and hospitality industry occupied a significant share in the structure of Ukraine's GDP. In particular, according to statistics, in 2019 the gross added value created in the hospitality industry amounted to 11.6% of the GDP of Ukraine, but starting from 2020, the domestic tourism and hospitality industry suffered significant losses due to the effects of the COVID-19 pandemic, which was typical of this industry worldwide.The purpose of the study is to systematize and generalize approaches to the development of innovative entrepreneurship in the tourism and hospitality industry in the context of overcoming modern challenges and threats.In the period of overcoming economic crises, innovations play a decisive role in the process of recovery and formation of the stability of the national economy. Economic crises provoked by financial instability, natural disasters, military aggressions, pandemics or other factors require adaptive and forward-looking reflections at both micro and micro levels. The experience of the previous decades shows that it was innovation in its various forms that proved to be the catalyst for recovery and transformation.Analysis of international practice shows that the tourism and hospitality industry is undergoing significant transformation under the influence of innovative entrepreneurship. Traditional models of the functioning of economic systems in modern conditions of technological development, growing competition, as well as challenges and threats are exposed to a set of negative factors, therefore, new opportunities appear when entrepreneurs use technologies, innovative approaches in conditions of constant change in consumer preferences. Under such conditions, the structure of the innovative landscape of the tourism and hospitality industry can be formed.In conclusion, innovative entrepreneurship is driving change and shaping the future of the tourism and hospitality industry. Tourism and hospitality entrepreneurs who use modern technology, equipment and unique expertise are well positioned to thrive in this evolving landscape. Despite the existence of certain threats, there are many opportunities in today's world for innovative growth, offering travelers new ways to explore interesting historical destinations.
Keywords: tourism; hospitality industry; innovative entrepreneurship; innovative landscape